Doing good does not preclude doing well: corporate responsibility and financial performance. Issue 4 (20th September 2018) - Lee, Jegoo; Graves, Samuel B.; Waddock, Sandra
Abstract : Purpose: This paper aims to propose and test a modified interpretation of long-standing issues on the corporate responsibility (CR)–corporate financial performance (CFP) relationship: companies involved in CR are in general no better and no worse in their level of financial performance than companies without such engagement because of the trade-off between benefit and cost at firm level and imbalance between supply and demand at industry (market) level. Design/methodology/approach: The authors apply this frame to a data set with more than 12, 000 observations over a 14-year period, using confidence intervals, as a useful and statistically valid approach for testing the null hypothesis. Findings: The present study's findings support neutrality between CR and CFP at the firm and industry levels, implying that a firm's CR involvement neither penalizes nor improves its CFP. Research limitations/implications: CR activities may provide windows of opportunity for companies but do not systematically improve financial performance. Practical implications: "Doing good" is not a panacea for corporate achievement with respect to market-facing activities. For firms to succeed, instead, they need to create and implement their business cases and models by converting their involvement in CR activities into drivers for better outcomes because investments in CR practices do alone not guarantee improved financial performance. Originality/value: The innovations in this study are twofold. Conceptually, this paper proposes a comprehensive approach for a neutral CR–CFP linkage. Empirically, it introduces a novel and appropriate method for testing neutrality. These will mark an important advance in the theoretical and empirical debates over CR and CFP.